إسهامات أبي الحسن علي بن الحسن الهنائ الأزدي المعروف بكراع النمل في اللغة ( توفى سنة 310هـ) - Ali Hassan, Elsayed Makki Elbishr; Suleiman, Hassan (Al-Hikmah International Journal of Islamic Studies And Human Sciences, 2019)
This research deals with a fraction of the contributions of a brilliant scientist in various arts of science, and his writings which includes many issues related to linguistic studies and jurisprudence of language and dictionaries. The researchers raises a number of questions, as follows: Who is the linguist that was named shepherd of ants? What are his linguistic contributions? What books did he write down? The researcher has drawn a number of objectives: Definition of ants' shepherds. Stand on his linguistic contributions. He addressed some of his books that worked in the language. The researcher took the descriptive analytical approach to reach the desired results. This research contributes to the field of science and knowledge provides an opportunity to get acquainted with this world that has not found its luck. It also shows the efforts of the ant sponsor, especially in the field of language studies. One of the most important results of this research is: Abu Hassan Ali bin Hassan Al-Hinai Muslim world has many contributions that have been recognized by only a few students of science and researchers. He wrote a number of works, the most important of which is the table in which we found many language is used and, arranged on the letters () ...أ، ب، ت، ث to the last letters, then abbreviated in the abstract book. His book Examples of strange weights of verbs in which a strange language. And the book of the Qoran. Book Organizer. His work also includes "Upholstered" ranks in six sections in the organs of the body and animal species and birds, and weapons and the sky and the earth. The researchers recommends the need to pay attention to the writings and contributions of linguists, especially those who do not find them in many books and scientific references, so that the students and researchers will benefit from their contributions.